2013
DOI: 10.1186/2193-7532-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing farmers’ behavior in rice seed selling in the market: a case study in the Tarai region of Nepald

Abstract: The importance of rice in food security and livelihoods of Nepalese people is well recognized but the seed supply system of this crop in the rural areas is poorly developed. To increase farmers' access to a wide range of rice varietal choices in a cost effective way, some farmers, organized in groups or cooperatives, have started producing and marketing rice seed through development projects in recent years. But very limited information has been published about the performance of the farmers in rice seed marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Quantitatively, as age increased by one year, the percentage of collective sale decreased by 1.6% points on average, holding other variables constant. This result conforms to Khanal and Maharjan (2013) and Martey et al. (2014) who found that younger farmers were more willing to participate in collective action in agriculture ( Xaba and Masuku, 2013 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Quantitatively, as age increased by one year, the percentage of collective sale decreased by 1.6% points on average, holding other variables constant. This result conforms to Khanal and Maharjan (2013) and Martey et al. (2014) who found that younger farmers were more willing to participate in collective action in agriculture ( Xaba and Masuku, 2013 ).…”
Section: Resultssupporting
confidence: 89%
“…This may be because larger farms can harvest more, thereby increasing marketable surplus ( Mukundi et al., 2013 ; Pochanasomboon et al., 2020 ; Vu et al., 2020 ; Kumse et al., 2021 ). Limitation in landholding typically impedes economic performance of a farm due to limited marketable surplus and insufficient ability to meet the standards of agricultural businesses ( Khanal and Maharjan, 2013 ; Pochanasomboon et al., 2020 ; Vu et al., 2020 ). Mathenge et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of specialized seed producers has been highlighted in other smallholder contexts for their ability to link the informal and formal systems and disseminate new crop varieties in a cost-effective way, albeit involving relatively small seed volumes (Otsyula et al, 2004;Nasirumbi et al, 2008;Khanal and Maharjan, 2014). In Peru's central highlands, the comparative advantage of seed specialists relates to their capacity to provide large volumes of seed of a limited number of common cultivars to specific users.…”
Section: The Role Of Different Farmer Types In the Seed Systemmentioning
confidence: 99%
“…The following study does not consider factors that influence grain quality when selling products such [7] the organization, number of livestock, of the head of the household, farmed land, availability to irrigation, and cost of seeds and [8] found factors that influence agricultural sales performance include geographic location, land area, grain business expertise, farming background, grain storage practices, and application of crop insurance, and [9] demonstrates that grain quality in Ethiopia is influenced by grain moisture content, temperature, initial conditions, insects, pests and fungi [10]. Studies on factors that influence the quality of grain/rice from a cultivation perspective include [11] and in terms of the application of shade, the application of N to panicles on the application of rice quality and [12] stated that the chlorophyll index at heading (CIG0) is an acceptable indicator of grain quality in rice.…”
Section: Introductionmentioning
confidence: 99%